Analisis Resepsi Komunitas Esports Mengenai Caster pada Konten Piala Menpora Esports 2020 - Abdurrahman; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Electronic technology development in Indonesia can be utilized for various aspects, one of the aspects is the existence of esports. Messages or informations that delivered by the caster in the esports match has various responses or reactions from the audiences. This research aims to determine Squad Hawk Eyes’ reception in interpreting the information given by the caster in Piala Menpora Esports 2020 at the grand final qualification. This research uses Stuart Hall's encoding- decoding theory and constructivism paradigm with a qualitative approach. The data collection technique uses in-depth interviews. In analyzing the data, the researcher uses the audience reception analysis with Stuart Hall's three categories: Dominant Hegemony, Negotiation, and Opposition. The results showed that informants who are in the position of Dominant Hegemony can receive messages from caster Pak Pulung and Kornet on the Menpora Esports Cup, related to the importance of the function of caster in esports matches, responses regarding esports matches must be equipped with caster and gimmick performed by caster Kornet and Pak Pulung. And informants who are in a negotiating position regarding caster esports are better for men.